Trend Research and Fashion Branding in the Modern Hyper-Consumption Society (ModaPalavra e-periódico, 2018)
Modern society is characterized by the generalization of fashion, which is the appreciation of the new. Fashion brands, therefore, are those whose products renew cyclically, constantly changing. In what sense these changes tend to occur is what trends researches, carried out professionally by style ‘bureaux’, try to predict. Contemporary society is also marked by hyperconsumption, in which individuals acquire much more than the functionality of products: they seek to experience sensations, feelings, share values, lifestyles, and personalities. In this sense, brands attribute much more than a signature to the products, but their management, or branding, aims to associate to their names a series of intangible attributes with which a group of consumers identifies. The purpose of this study, in this scenario, is to describe and analyze the relationships between fashion, hyperconsumption, branding, and trends research in modern society.
Keywords: fashion trends; branding; modern society